2004
DOI: 10.2527/2004.8271997x
|View full text |Cite
|
Sign up to set email alerts
|

Ileal amino acid digestibility and performance of growing pigs fed wheat-based diets supplemented with xylanase

Abstract: Two experiments were conducted to determine the effect of supplementation of xylanase to a wheat-based diet on the apparent ileal digestibility (AID) of AA and the performance of growing pigs fed diets limiting in AA. In Exp. 1, eight pigs (average initial BW = 20.5+/-1.2 kg) fitted with a simple T-cannula at the distal ileum, were fed four diets according to a repeated 4 x 4 Latin square design. Diet 1 was a basal diet that contained 97.6% wheat. Diets 2, 3, and 4 were the basal diet supplemented with xylanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 20 publications
6
55
1
9
Order By: Relevance
“…Esse mecanismo pode explicar, em parte, o aumento observado na digestibilidade ileal dos aminoácidos. Além disso, a ação da xilanase pode variar entre aminoácidos, uma vez que a quantidade de polissacarídeos não amiláceos na dieta altera a amplitude das respostas (Yin et al, 2000a;Barrera et al, 2004).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Esse mecanismo pode explicar, em parte, o aumento observado na digestibilidade ileal dos aminoácidos. Além disso, a ação da xilanase pode variar entre aminoácidos, uma vez que a quantidade de polissacarídeos não amiláceos na dieta altera a amplitude das respostas (Yin et al, 2000a;Barrera et al, 2004).…”
Section: Resultsunclassified
“…As equações obtidas confirmam que a ação da xilanase aumenta a digestibilidade ileal dos aminoácidos essenciais e não essenciais em 2 a 3%. No entanto, os estudos indicam variações quanto aos aminoácidos que apresentam melhor digestibilidade ileal aparente (Yin et al, 2000a;Barrera et al, 2004;Nortey et al, 2008;Woyengo et al, 2008). Um dos mecanismos de ação da xilanase sobre a digestibilidade dos aminoácidos está relacionado à redução da barreira física entre enzimas e substrato (Yin et al, 2000b).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Some reports show that a reduction of four or less CP percentage units in corn-soybean meal (SBM) diets does not affect the performance and carcass characteristics of finishing pigs (Tuitoek et al, 1997;Knowles et al, 1998;Le Bellego et al, 2002). Moreover, Barrera et al (2004) showed that free Lys and Thr could replace SBM completely in wheat diets for growing pigs without affecting their performance. However, other reports show a decreased performance and thicker back fat when CP was reduced by four or more percentage units in cornor sorghum-SBM diets (e.g., Brudevold and Southern, 1994;Tuitoek et al, 1997;Yue and Qiao, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report shows that the dietary content of Leu and Lys affects the absorption of Lys (García-Villalobos et al, 2012). F-AA diets not only contain lower Arg and Leu levels but also a high percentage of free Lys, from 44% (Kerr et al, 2003) to 70% (Barrera et al, 2004) of total Lys. Since protein-bound AA need to be released by pancreatic and intestinal enzymes prior to their absorption, free AA may be absorbed faster and their availability for protein synthesis could be higher (Rerat et al, 1992).…”
Section: Introductionmentioning
confidence: 99%